STN local field potential recordings from awake patients with Parkinson’s, ON and OFF meds, and during 130 Hz DBS - Wiest, C; Torrecillos, F; Pogosyan, A; Baig, F; Pereira, E; Morgante, F; Ashkan, K; Tan, H (University of Oxford, 2022)
Subthalamic local field potential recordings from awake patients with Parkinson’s disease while leads were externalised. In 30 hemispheres, this data was recorded ON and OFF dopaminergic medication and in 26 hemispheres before and during 130 Hz deep brain stimulation of the subthalamic nucleus.